Development of a new performance metric for golf clubs using COR maps and impact probability data - Lambeth, J.; Brunski, J.; Brekke, D. (Proceedings, 2018)
Golf clubs are often evaluated by many methods to determine their performance. For drivers in particular, the primary performance indicator is ball speed, which is directly related to distance. Golf club manufacturers make many claims about how extra ball speed is achieved. For example, these may include: design features, face thickness, materials, center of gravity location, and moments of inertia. This paper proposes a new method to evaluate the performance of golf clubs from a single metric. With the benefits of modern launch monitors, accurate impact location data can be captured very efficiently. Using this, along with COR (coefficient of restitution) map testing, the Expected Value of COR can be calculated for a golfer or population of golfers. The "Expected COR" metric takes into account many engineering properties of a particular club that affect ball speed, along with the impact variation of the golfer, to give a single score for rating.